Deciphering Metabolic Responses in Traumatic Brain Injury Patients With Different Severity Using 1H NMR-Based Serum Metabolomics - Huan Zhou; Dongdong Sun; Dongmei Wang; Zirui Zhu; Xuelian Hong; Rui Fang; Hua Wang; Minghui Li (Scientifica)
The analysis of metabolites presents a promising opportunity to gain insight into the neuropathophysiology of individuals affected by traumatic brain injury (TBI). In order to elucidate the underlying pathophysiologic mechanisms and identify serum biomarkers associated with TBI, we conducted a comprehensive investigation utilizing a 1H nuclear magnetic resonance (NMR)–based metabolomics approach and ELISA analysis of serum samples obtained within 24 h postinjury from a cohort of participants with varying degrees of TBI severity. Our findings revealed that the decrease of isoleucine, valine, tryptophan, and histidine, as well as the increase of lactate, were proportional to the severity of TBI. In addition, creatine phosphate showed promise in specifically distinguishing moderate TBI from controls, while glutamine and the lactate-to-pyruvate ratio demonstrated excellent performance in diagnosing severe TBI from controls. Pathway analysis revealed disruptions in the ketone body metabolism, carnitine synthesis, butyrate metabolism, and citric acid cycle across mild to severe TBI patients. Moreover, our findings suggest an upregulation of the cytokines IL-1β, IL-6, and TNF-α following TBI, displaying correlations with lactate, 5-aminopentanoate, glucose, and creatinine metabolites. This study offers a novel concept and theoretical framework by leveraging serum metabolites to enhance the objective, rapid and reliable assessment of TBI severity. The clinical implications of this research are significant, as it facilitates the diagnosis and prognosis of TBI patients across a spectrum of severity levels.